GM-CSF Promotes the Expansion and Differentiation of Cord Blood Myeloid-Derived Suppressor Cells, Which Attenuate Xenogeneic Graft-vs.-Host Disease - Park, Mi-Young; Lim, Bang-Geul; Kim, Su-Yeon; Sohn, Hyun-Jung; Kim, Sueon; Kim, Tai-Gyu (Frontiers in Immunology, 2019)
Myeloid-derived suppressor cells (MDSCs) are increased in tumor patients. A lot of study showed to generate MDSCs from human peripheral blood mononuclear cells (PBMCs) by various cytokine combinations. However, it has been not yet reported to expand human MDSCs with large scale (more than 108 cells from an individual sample) to apply in clinics. We investigated which cytokine combinations among GM-CSF/SCF, G-CSF/SCF or M-CSF/SCF induce to efficiently expand and differentiate human MDSCs from umbilical cord blood (CB) CD34+ cells. The CD34+ cells (1x105) cultured with GM-CSF/SCF showed the most efficient expansion to reach up to 108 cells from 1 unit of CB for 3 weeks and then continuous differentiation into MDSCs (HLA-DRlowCD11b+CD33+) by high cell concentration (5x105) from 4 weeks to 6 weeks since culture. Importantly, the CD34+ cells cultured with GM-CSF/SCF for 6 weeks (MDSCs) represented the most suppressive function for T cell proliferation and the most potent expression of immunosuppressive molecules such as iNOS, Arginase1 and IDO to compare with those with G-CSF/SCF or M-CSF/SCF. The MDSCs secreted IL-10, TGB-β and VEGF. The infusion of MDSCs significantly prolonged the survival and decreased the GVHD score in the NSG xenogeneic GVHD model. The MDSCs increased IL-10 and TGF- β but decreased the level of TNF-α and IL-6 in the serum of GM-MDSCs treated mice. Notably, FoxP3 expressing regulatory T (Treg) cells were increased while IFN-γ (Th1) and IL-17 (Th17) producing T cells were decreased in the splenocytes of MDSCs treated mice to compare with untreated GVHD mice. Therefore, our results demonstrate that human MDSCs generated by GM-CSF/SCF have a sufficient amount and potent immunosuppressive function, suggesting a possible treatment for inflammatory diseases such as GVHD in the clinics.